Student teachers’ perceptions of a Wits rural teaching experience project: What to learn and improve - Nkambule, T.C. (South African Journal of Higher Education, 2017)
In South Africa all universities send education student teachers to schools for teaching practice as part of their preparation for teaching. Of concern is the lack of research investigating pre-service teachers’ experiences of teaching practice, especially in rural and farm schools. Several rural teaching practice projects have been established by various teacher education training institutions in South Africa, in order to introduce student teachers to rurality and rural and farm schools. The introduction of the projects suggests an acknowledgement of varied school contexts and pedagogies, and the importance of making education student teachers aware of them. The project use a qualitative approach and semi-structured reflective discussions and reflective journals to collect data. The findings show that education student teachers want to be part of the rural community and schools, rather than being ‘tourists’ and ‘scientists’. Collaboration between pre-service and in-service teachers is identified as crucial to share teaching skills.